IMPLEMENTASI PROGRAM PENTA HELIX DALAM PROGRAM MEDIA DAN PUBLIKASI DESA - Nani Harlinda Nurdin; Faizah Mahi; Dian Mirnawaty Sultan; Zulkarnain Hamson (Yayasan Education and Social Center, 2023)
Alumni Family Association (IKA) of the Faculty of Social and Political Sciences (FISIP) Hasanuddin University (UNHAS) involving members from representatives of State (PTN) and Private Universities (PTS), and the Regional Management Council (DPD) of Indonesian Online Journalists (JOIN) Bone Regency, South Sulawesi (Sulsel), led by Zulkarnain Hamson, Chair of the Community Service Team (PKM), with three facilitator lecturers, carried out Village Journalism training with the theme: